Age-related differences in functional balance and muscular strength - Sohn, J. H.; Choi, H. M.; Hurr, C.; Kim, S. (Medicina dello Sport, 2020)
BACKGROUND: The decreased physical capability such as a decrease in lower extremity strength with advancing age are frequently accompanied with mobility problems. Unstable postural stability and poor motor performance influence the likelihood of falls among older adults. The aim of the present study was to compare postural stability performance and lower extremity strength across two age groups and was to relate postural stability performance and lower extremity strength. METHODS: Fifty-five health adults (27 young and 28 old adults) participated in this experiment. Dynamic and static postural stability and isokinetic strength at ankle (30o/s) and knee (60o/s) joints were collected. RESULTS: The results indicated that there were significant group effects in isokinetic ankle and knee strengths, and dynamics and static balance. In addition, there were high correlations between strength and postural stability. CONCLUSIONS: The present study concluded that, with advancing age, an increase in muscular leg strength may be the key component in improving balance performance.